Steel material and soft magnetic component

JP2025001450APending Publication Date: 2025-01-08NIPPON STEEL CORPORATION
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2023101047
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-06-20
Publication Date
2025-01-08

AI Technical Summary

Benefits of technology

【0019】 本開示の鋼材では、優れた磁気特性及び優れた冷間鍛造性が得られ、さらに、優れた切り屑処理性が得られる。本開示の軟磁性部品は、上述の鋼材からなる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025001450000005
    Figure 2025001450000005
  • Figure 2025001450000006
    Figure 2025001450000006
  • Figure 2025001450000007
    Figure 2025001450000007
Patent Text Reader

Abstract

To provide a steel material that exhibits superior magnetization characteristics and superior cold forgeability while also achieving superior chip processing capability.SOLUTION: A steel material disclosed herein comprises, in mass%, C: 0.0300% or less, Si: 0.20% or less, Mn: 0.10-0.50%, P: 0.030% or less, S: 0.030% or less, Al: 0.050% or less, N: less than 0.0080%, O: 0.030% or less, and Bi: 0.0010-0.0300%, with the balance being Fe and impurities. The composite precipitates of Bi and MnS have a particle size of 1.0-10.0 μm and a number density of 0.9-300.0 pieces / mm2.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a steel material and a soft magnetic part, and more particularly to a soft magnetic steel material and a soft magnetic part manufactured using the steel material as a material. [Background technology]

[0002] Soft magnetic parts are used in electrical components of automobiles and industrial machines, etc. Examples of such soft magnetic parts include solenoids used in automatic transmissions, electromagnetic clutches, brakes, etc., iron core materials for parts such as relays and electromagnetic valves, magnetic shielding materials, electric actuator materials, motor components, sensor components, etc.

[0003] Soft magnetic parts are required to have excellent magnetic properties. Specifically, they are required to have high magnetic flux density and low hysteresis loss (i.e. low coercive force). Soft magnetic steel is used as the material for magnetic parts that require such properties. This steel has improved magnetic properties by reducing the content of alloy elements.

[0004] A method for manufacturing a soft magnetic part using soft magnetic steel as a material is, for example, as follows: The steel is subjected to a lubrication treatment, and then wire drawing is performed. The steel after wire drawing is subjected to cold forging to manufacture an intermediate product having a rough shape close to the final shape of the soft magnetic part. The intermediate product is cut to adjust the shape of the intermediate product to the final shape. The intermediate product after cutting is subjected to magnetic annealing as necessary. The soft magnetic part is manufactured by the above manufacturing steps.

[0005] As described above, the steel material used to make soft magnetic parts is subjected to cold forging and cutting. Therefore, the steel material used to make soft magnetic parts is required to have not only excellent magnetic properties but also excellent cold forgeability and excellent cutting workability. The steel material used to make soft magnetic parts has a low content of alloy elements, so it is soft and has high toughness. Therefore, there is a particular demand for improved cutting workability.

[0006] Steel materials for soft magnetic parts that focus on improving magnetic properties, cold forgeability, cutting workability, etc. have been proposed in, for example, JP-B-51-16363 (Patent Document 1), JP-A-2003-55745 (Patent Document 2), JP-A-2007-46125 (Patent Document 3), and JP-A-2018-76556 (Patent Document 4).

[0007] The steel material disclosed in Patent Document 1 contains C: 0.05% or less, Si: 1.0% or less, and Bi: 0.03-0.40%, and further contains one or more selected from the group consisting of Pb: 0.03-0.40%, Se: 0.03-0.40%, Te: 0.01-0.10%, and Ca: 0.0005-0.0100%, with the balance being Fe and impurities. Patent Document 1 states that by containing 0.03% or more Bi, the machinability is improved while maintaining the magnetic properties.

[0008] The steel material disclosed in Patent Document 2 satisfies C: 0.05% or less, Si: 0.1% or less, Mn: 0.10-0.50%, P: 0.030% or less, S: 0.010-0.15%, Al: 0.01% or less, N: 0.005% or less, O: 0.02% or less, the balance being substantially Fe, and Mn / S is 3.0 or more. Furthermore, the ferrite grain size is 100 μm or more, and MnS precipitates with a grain size of 0.2 μm or more are present in the ferrite grains at a rate of 0.02-0.5 / μm. 2 Furthermore, the average grain size of the MnS precipitates is 0.05 to 4 μm. Patent Document 2 describes that the above-mentioned configuration provides excellent magnetic properties, excellent cold forgeability, and excellent machinability.

[0009] The steel material disclosed in Patent Document 3 contains C: 0.0015-0.02%, Mn: 0.15-0.5%, and S: 0.015-0.1%, and has a mass ratio of Mn to S (Mn / S) of 5.7 or more. Furthermore, the metal structure is a ferritic single phase structure, and the number of FeS precipitates with a major axis of 0.1 μm or more is 5,000 / mm. 2The following is the description in Patent Document 3. It is described that the above-mentioned configuration provides excellent magnetic properties, excellent cold forgeability, and further provides excellent cutting workability.

[0010] The steel material disclosed in Patent Document 4 satisfies C: 0.0001-0.05 mass%, Si: more than 0-0.5 mass%, Mn: 0.1-0.5 mass%, P: more than 0-0.02 mass%, S: more than 0-0.1 mass%, Al: more than 0-0.05 mass%, and N: more than 0.01-0.1 mass%, with the remainder being Fe and impurities, and has a ferrite structure area ratio of 95.0% or more. This steel material further satisfies formula (1) ([N]-(1 / 2[Al])>0.01). Patent Document 4 describes that the steel material has excellent machinability and exhibits excellent magnetic properties after magnetic annealing. [Prior art documents] [Patent documents]

[0011] [Patent Document 1] Special Publication No. 51-16363 [Patent Document 2] JP 2003-55745 A [Patent Document 3] JP 2007-46125 A [Patent Document 4] JP 2018-76556 A Summary of the Invention [Problem to be solved by the invention]

[0012] By the way, in line with recent global efforts toward carbon neutrality, the manufacturing process for soft magnetic parts is being made using a method that uses less CO than hot forging. 2 Cold forging, which produces less emissions, is becoming more common. Furthermore, as electrical components become more energy-efficient and perform better, the shapes of soft magnetic parts are becoming more complex. As the shapes become more complex, the forging load in cold forging and the cutting load in cutting also increase.

[0013] One of the indicators of cutting workability is chip disposability. Chip disposability means the ease of disposing of chips generated by cutting work. If the chips generated by cutting work are too long, they tend to get tangled with the base material and tools. As a result, scratches are generated in the soft magnetic parts that are the products, and the tools are damaged. On the other hand, if the chips are too short, they are difficult to discharge from the cutting part, causing clogging and damaging the tools. Recently, automation of cutting work has progressed. Therefore, if the chips get tangled with the tools or the like or clogging occurs, it becomes necessary for the cutting equipment to be temporarily stopped and the worker to remove the chips, which reduces productivity. Therefore, the steel material that is the material of the soft magnetic parts is required to have excellent magnetic properties and excellent cold forgeability, as well as excellent chip disposability that breaks the chips into appropriate lengths during cutting work.

[0014] Patent Documents 1 to 4 do not specifically discuss a steel material that can provide excellent magnetic properties, excellent cold forgeability, and also excellent chip disposability.

[0015] An object of the present disclosure is to provide a steel material that has excellent magnetic properties, excellent cold forgeability, and further excellent chip disposability, and to provide a soft magnetic part made from that steel material. [Means for solving the problem]

[0016] The steel material according to the present disclosure is Chemical composition, in mass%, C: 0.0300% or less, Si: 0.20% or less, Mn: 0.10-0.50%, P: 0.030% or less, S: 0.030% or less, Al: 0.050% or less, N: Less than 0.0080%, O: 0.030% or less, and Bi: 0.0010 to 0.0300% The balance is Fe and impurities. The number density of composite precipitates containing Bi and MnS and having a circle equivalent diameter of 1.0 to 10.0 μm is 0.9 to 300.0 pieces / mm 2 It is.

[0017] The steel material according to the present disclosure is Chemical composition, in mass%, C: 0.0300% or less, Si: 0.20% or less, Mn: 0.10-0.50%, P: 0.030% or less, S: 0.030% or less, Al: 0.050% or less, N: Less than 0.0080%, O: 0.030% or less, and Bi: 0.0010 to 0.0300% Further, it contains one or more selected from the group consisting of Groups 1 to 4, The balance is Fe and impurities. The number density of composite precipitates containing Bi and MnS and having a circle equivalent diameter of 1.0 to 10.0 μm is 0.9 to 300.0 pieces / mm 2 It is. [Group 1] Cu: 0.30% or less, Ni: 0.20% or less, Cr: 0.20% or less, and Mo: 0.05% or less, one or more selected from the group consisting of [Group 2] B: 0.010% or less, Ti: 0.010% or less, Nb: 0.010% or less, and V: 0.010% or less, one or more selected from the group consisting of [Group 3] Ca: 0.010% or less, Te: 0.010% or less, Zr: 0.010% or less, and Mg: 0.010% or less, one or more selected from the group consisting of [Group 4] Pb:0.090% or less

[0018] The soft magnetic component according to the present disclosure is made of the above-mentioned steel material. Effect of the Invention

[0019] The steel material of the present disclosure has excellent magnetic properties and excellent cold forgeability, and further has excellent chip disposability. The soft magnetic part of the present disclosure is made of the above-mentioned steel material. [Brief description of the drawings]

[0020] [Figure 1] FIG. 1 is a plan view and a side view of a test piece used in cold forgeability evaluation test 2 (limit compression ratio) of the examples. [Diagram 2] FIG. 2 is a plan view and a side view of a ring-shaped test piece used in a magnetic property evaluation test in the examples. [Diagram 3] FIG. 3 is a plan view and a side view of a test piece prepared in a chip-disposability evaluation test in the examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0021] The present inventors have conducted research into a steel material that can provide excellent magnetic properties, excellent cold forgeability, and further excellent chip disposability.

[0022] The present inventors first investigated, from the viewpoint of chemical composition, steel that can be used as a material for soft magnetic parts and that can provide excellent magnetic properties and excellent cold forgeability. As a result, the steel was found to have the following composition by mass: C: 0.0300% or less, Si: 0.20% or less, Mn: 0.10-0.50%, P: 0.030% or less, S: 0.030% or less, Al: 0.050% or less, N: less than 0.0080%, O: 0.030% or less, Bi: 0.0010-0.0300%, Cu: 0-0.30%, Ni: 0-0.20%, Cr: 0-0.20%, Mo: 0-0.05%. It was believed that excellent magnetic properties and excellent cold forgeability could be obtained if a steel material had a chemical composition consisting of the following: B: 0-0.010%, Ti: 0-0.010%, Nb: 0-0.010%, V: 0-0.010%, Ca: 0-0.010%, Te: 0-0.010%, Zr: 0-0.010%, Mg: 0-0.010%, Pb: 0-0.090%, and the remainder being Fe and impurities.

[0023] Therefore, the present inventors have further investigated means for obtaining excellent chip disposability in a steel material having the above-mentioned chemical composition, and as a result, the present inventors have obtained the following findings.

[0024] In order to improve chip disposability, a composite precipitate containing Bi and MnS is effective. Hereinafter, the composite precipitate containing Bi and MnS is also referred to as a "specific composite precipitate." During cutting of steel, the Bi in the specific composite precipitates melts or becomes embrittled. The melting and embrittlement of Bi forms a stress concentration area between the specific composite precipitates and the base material. This promotes separation of chips from the base material. Furthermore, the effect of Bi on the magnetic properties and cold forgeability of the steel is small. Therefore, the specific composite precipitates improve chip disposal during cutting.

[0025] Based on the above findings, the present inventors further investigated and examined the relationship between the size and number density of the specific complex precipitates and the chip disposability, and as a result, the present inventors further obtained the following findings.

[0026] Among the specific composite precipitates, those having a circle equivalent diameter of 1.0 to 10.0 μm contribute significantly to improving chip disposability. The number density ND of the specific composite precipitates having a circle equivalent diameter of 1.0 to 10.0 μm is 0.9 to 300.0 precipitates / mm 2 If so, there is an appropriate amount of specific composite precipitates that act as starting points for chips to separate from the base material during cutting. Therefore, during cutting, the chips separate from the base material at an appropriate length that is neither too long nor too short. Therefore, excellent chip disposability is obtained.

[0027] The steel material and soft magnetic part of this embodiment have been completed based on the above technical concept, and have the following configuration.

[0028] [1] Chemical composition, in mass%, C: 0.0300% or less, Si: 0.20% or less, Mn: 0.10-0.50%, P: 0.030% or less, S: 0.030% or less, Al: 0.050% or less, N: Less than 0.0080%, O: 0.030% or less, and Bi: 0.0010 to 0.0300% The balance is Fe and impurities. The number density of composite precipitates containing Bi and MnS and having a circle equivalent diameter of 1.0 to 10.0 μm is 0.9 to 300.0 pieces / mm 2 That is, Steel material.

[0029] [2] Chemical composition, in mass%, C: 0.0300% or less, Si: 0.20% or less, Mn: 0.10-0.50%, P: 0.030% or less, S: 0.030% or less, Al: 0.050% or less, N: Less than 0.0080%, O: 0.030% or less, and Bi: 0.0010 to 0.0300% Further, it contains one or more selected from the group consisting of Groups 1 to 4, The balance is Fe and impurities. The number density of composite precipitates containing Bi and MnS and having a circle equivalent diameter of 1.0 to 10.0 μm is 0.9 to 300.0 pieces / mm 2 That is, Steel material. [Group 1] Cu: 0.30% or less, Ni: 0.20% or less, Cr: 0.20% or less, and Mo: 0.05% or less, one or more selected from the group consisting of [Group 2] B: 0.010% or less, Ti: 0.010% or less, Nb: 0.010% or less, and V: 0.010% or less, one or more selected from the group consisting of [Group 3] Ca: 0.010% or less, Te: 0.010% or less, Zr: 0.010% or less, and Mg: 0.010% or less, one or more selected from the group consisting of [Group 4] Pb:0.090% or less

[0030] [3] The steel material according to [2], The chemical composition contains the first group, Steel material.

[0031] [4] The steel material according to [2] or [3], The chemical composition contains the second group, Steel material.

[0032] [5] The steel material according to any one of [2] to [4], The chemical composition contains the third group, Steel material.

[0033] [6] The steel material according to any one of [2] to [5], The chemical composition contains the fourth group, Steel material.

[0034] [7] The steel material according to any one of [1] to [6], Bp defined by formula (1) is 4.00 to 75.00; Steel material. Bp = 10 × (Mn + 10 × S + 240 × Bi) (1) Here, each element symbol in formula (1) is substituted with the content of the corresponding element in mass %.

[0035] [8] A steel material according to any one of [1] to [7], The average grain size number of ferrite is less than 7. Steel material.

[0036] [9] [1] to [8] The steel material according to any one of the above. Soft magnetic parts.

[0037] The steel material of this embodiment will be described in detail below. Note that "%" for elements means mass % unless otherwise specified.

[0038] [Features of the steel material of this embodiment] The steel material of this embodiment satisfies the following characteristics 1 and 2. (Feature 1) The chemical composition is, in mass%, C: 0.0300% or less, Si: 0.20% or less, Mn: 0.10-0.50%, P: 0.030% or less, S: 0.030% or less, Al: 0.050% or less, N: less than 0.0080%, O: 0.030% or less, Bi: 0.0010-0.0300%, Cu: 0-0.30%, Ni: 0-0.20%, Cr: 0-0.20%, Mo: 0-0.05%, B: 0-0.010%, Ti: 0-0.010%, Nb: 0-0.010%, V: 0-0.010%, Ca: 0-0.010%, Te: 0-0.010%, Zr: 0-0.010%, Mg: 0-0.010%, Pb: 0-0.090%, and the balance is Fe and impurities. (Feature 2) The grain size of the composite precipitates of Bi and MnS is 1.0 to 10.0 μm, and the number density is 0.9 to 300.0 precipitates / mm 2 It is. Features 1 and 2 will be explained below.

[0039] [(Feature 1) Chemical composition] The steel material of this embodiment contains the following elements.

[0040] C: 0.0300% or less Carbon (C) increases the strength of steel. However, if the C content exceeds 0.0300%, C dissolves in the steel, causing strain aging hardening and reducing the cold forgeability of the steel. If the C content exceeds 0.0300%, cementite is formed in excess, further reducing the magnetic properties of the steel. Therefore, the C content is 0.0300% or less. The C content is preferably as low as possible. However, excessive reduction in the C content reduces productivity and increases manufacturing costs. Therefore, in consideration of normal industrial production, the preferred lower limit of the C content is more than 0%, more preferably 0.0001%, more preferably 0.0002%, more preferably 0.0003%, more preferably 0.0005%, and more preferably 0.0010%. The upper limit of the C content is preferably 0.0250%, more preferably 0.0200%, still more preferably 0.0150%, and still more preferably 0.0100%.

[0041] Si:0.20% or less Silicon (Si) deoxidizes steel. Si also improves the magnetic properties of steel. Even if even a small amount of Si is contained, the above effects can be obtained to some extent. However, if the Si content exceeds 0.20%, the hardness of the steel increases excessively and the cold forgeability decreases. Therefore, the Si content is 0.20% or less. The lower limit of the Si content is preferably more than 0%, more preferably 0.01%, more preferably 0.02%, and even more preferably 0.03%. The upper limit of the Si content is preferably 0.15%, more preferably 0.10%, and further preferably 0.05%.

[0042] Mn: 0.10~0.50% Manganese (Mn) deoxidizes steel. Furthermore, Mn combines with S in steel to form MnS, suppressing embrittlement caused by S. This improves cold forgeability. Furthermore, MnS becomes a stress concentration source during cutting, improving the machinability of steel. If the Mn content is less than 0.10%, this effect cannot be fully obtained. On the other hand, if the Mn content exceeds 0.50%, excessive MnS is generated. In this case, the excess MnS inhibits the grain growth of ferrite. As a result, the magnetic properties of the steel deteriorate. Therefore, the Mn content is 0.10 to 0.50%. The lower limit of the Mn content is preferably 0.12%, more preferably 0.15%, and further preferably 0.20%. The upper limit of the Mn content is preferably 0.45%, more preferably 0.40%, and further preferably 0.30%.

[0043] P:0.030% or less Phosphorus (P) is an impurity. P segregates at grain boundaries and reduces the magnetic properties and cold forgeability of steel. Therefore, the P content is limited to 0.030% or less. The P content is preferably as low as possible. However, excessive reduction in the P content reduces productivity and increases production costs. Therefore, in consideration of normal industrial production, the lower limit of the P content is preferably more than 0%, more preferably 0.001%, more preferably 0.002%, and even more preferably 0.003%. The upper limit of the P content is preferably 0.025%, more preferably 0.020%, and further preferably 0.015%.

[0044] S: 0.030% or less Sulfur (S) combines with Mn to form MnS, which improves the machinability of steel. However, if the S content exceeds 0.030%, an excessive amount of MnS is produced, which inhibits the grain growth of ferrite. This reduces the magnetic properties of the steel. Therefore, the S content is limited to 0.030% or less. The S content is preferably as low as possible. However, excessive reduction in the S content reduces productivity and increases manufacturing costs. Therefore, in consideration of normal industrial production, the preferred lower limit of the S content is more than 0%, more preferably 0.001%, more preferably 0.002%, and even more preferably 0.003%. The upper limit of the S content is preferably 0.025%, more preferably 0.020%, further preferably 0.015%, and further preferably 0.009%.

[0045] Al: 0.050% or less Aluminum (Al) deoxidizes steel. However, if the Al content exceeds 0.050%, Al bonds with N in the steel to form AlN. AlN has a pinning effect, which refines the crystal grains and reduces the magnetic properties of the steel. Therefore, the Al content is limited to 0.050% or less. In order to suppress the pinning effect of AlN, it is preferable that the Al content is small. On the other hand, as described above, Al has a deoxidizing effect. Therefore, in consideration of the manufacturing advantage due to the deoxidizing effect, the preferable lower limit of the Al content is 0.001%, more preferably 0.003%, and further preferably 0.005%. The upper limit of the Al content is preferably 0.040%, more preferably 0.030%, further preferably 0.020%, and further preferably 0.010%.

[0046] N: Less than 0.0080% Nitrogen (N) is an impurity. N dissolves in steel and reduces the cold forgeability of the steel due to strain aging hardening. N also combines with Al to form AlN, which refines the crystal grains and reduces the magnetic properties of the steel. Therefore, the N content is less than 0.0080%. The lower limit of the N content is preferably more than 0%, more preferably 0.0001%, even more preferably 0.0005%, and even more preferably 0.0010%. The upper limit of the N content is preferably 0.0060%, more preferably 0.0050%, and further preferably 0.0040%.

[0047] O: 0.030% or less Oxygen (O) is an impurity. O combines with Al or Si in steel to form oxides. These oxides reduce the cold forgeability and magnetic properties of the steel. Therefore, the O content is 0.030% or less. The O content is preferably as low as possible. However, excessive reduction in the O content reduces productivity and increases production costs. Therefore, in consideration of normal industrial production, the lower limit of the O content is preferably more than 0%, more preferably 0.001%, even more preferably 0.002%, even more preferably 0.003%, and even more preferably 0.004%. The upper limit of the O content is preferably 0.020%, more preferably 0.015%, and further preferably 0.010%.

[0048] Bi: 0.0010~0.0300% Bi combines with MnS to form specific complex precipitates, improving the chip disposability of the steel material. If the Bi content is less than 0.0010%, the above effect is not sufficiently obtained. On the other hand, if the Bi content exceeds 0.0300%, an excessive amount of specific complex precipitates is generated. In this case, the cold forgeability and magnetic properties of the steel material are deteriorated. Therefore, the Bi content is 0.0010 to 0.0300%. The lower limit of the Bi content is preferably 0.0015%, more preferably 0.0020%, further preferably 0.0025%, and further preferably 0.0030%. The upper limit of the Bi content is preferably 0.0250%, more preferably 0.0200%, more preferably 0.0100%, more preferably 0.0080%, and even more preferably 0.0050%.

[0049] The balance of the chemical composition of the steel material of the present embodiment is composed of Fe and impurities. Here, the term "impurities" refers to substances that are mixed in from raw materials such as ores and scraps or from the manufacturing environment during industrial production of the steel material, but are not intentionally contained and are permissible within a range that does not adversely affect the steel material of the present embodiment.

[0050] [About optional elements] The chemical composition of the steel material of this embodiment may further contain one or more elements selected from the group consisting of first to fourth groups. [Group 1] Cu: 0.30% or less, Ni: 0.20% or less, Cr: 0.20% or less, and Mo: 0.05% or less, one or more selected from the group consisting of [Group 2] B: 0.010% or less, Ti: 0.010% or less, Nb: 0.010% or less, and V: 0.010% or less, one or more selected from the group consisting of [Group 3] Ca: 0.010% or less, Te: 0.010% or less, Zr: 0.010% or less, and Mg: 0.010% or less, one or more selected from the group consisting of [Group 4] Pb:0.090% or less The first to fourth groups will be explained below.

[0051] [Group 1 (Cu, Ni, Cr and Mo)] The chemical composition of the steel material of this embodiment may contain, in place of a portion of Fe, one or more elements selected from the group consisting of Cu, Ni, Cr and Mo. Any of these elements increases the strength of the steel material.

[0052] Cu:0.30% or less Copper (Cu) is an optional element and may not be contained. In other words, the Cu content may be 0%. When contained, Cu increases the strength of the steel material by solid solution strengthening. Even if even a small amount of Cu is contained, the above effect can be obtained to a certain degree. However, if the Cu content exceeds 0.30%, the hot workability of the steel material decreases. Therefore, the Cu content is 0 to 0.30%, and when contained, the Cu content is 0.30% or less. The lower limit of the Cu content is preferably 0.01%, more preferably 0.02%, and further preferably 0.03%. The upper limit of the Cu content is preferably 0.28%, more preferably 0.25%, and further preferably 0.20%.

[0053] Ni: 0.20% or less Nickel (Ni) is an optional element and does not have to be contained. In other words, the Ni content may be 0%. When contained, Ni increases the strength of the steel material by solid solution strengthening. If even a small amount of Ni is contained, the above effects can be obtained to a certain extent. However, if the Ni content exceeds 0.20%, the cold forgeability of the steel material decreases, and therefore the Ni content is 0 to 0.20%, and if Ni is contained, the Ni content is 0.20% or less. The lower limit of the Ni content is preferably 0.01%, more preferably 0.02%, and further preferably 0.03%. The upper limit of the Ni content is preferably 0.18%, more preferably 0.15%, further preferably 0.13%, and further preferably 0.10%.

[0054] Cr:0.20% or less Chromium (Cr) is an optional element and does not have to be contained. In other words, the Cr content may be 0%. When Cr is contained, Cr increases the strength of the steel material by solid solution strengthening. Even if even a small amount of Cr is contained, this effect can be obtained to a certain extent. However, if the Cr content exceeds 0.20%, the cold forgeability of the steel material decreases, and therefore the Cr content is 0 to 0.20%, and if contained, the Cr content is 0.20% or less. The lower limit of the Cr content is preferably 0.01%, more preferably 0.02%, and further preferably 0.03%. The upper limit of the Cr content is preferably 0.18%, more preferably 0.15%, further preferably 0.13%, and further preferably 0.10%.

[0055] Mo: 0.05% or less Molybdenum (Mo) is an optional element and does not have to be contained. In other words, the Mo content may be 0%. When contained, Mo increases the strength of the steel material by solid solution strengthening. Even if even a small amount of Mo is contained, the above effects can be obtained to a certain extent. However, if the Mo content exceeds 0.05%, the cold forgeability of the steel material decreases, and therefore the Mo content is 0 to 0.05%, and if Mo is contained, the Mo content is 0.05% or less. The lower limit of the Mo content is preferably 0.01%, and more preferably 0.02%. The upper limit of the Mo content is preferably 0.04%, and more preferably 0.03%.

[0056] [Group 2 (B, Ti, Nb and V)] The chemical composition of the steel material according to the present embodiment may further contain, instead of a part of Fe, one or more elements selected from the group consisting of B, Ti, Nb, and V. Any of these elements fixes solute N and suppresses strain age hardening.

[0057] B: 0.010% or less Boron (B) is an optional element and may not be contained. In other words, the B content may be 0%. When B is contained, B forms nitrides to fix N. This suppresses strain age hardening. Even if even a small amount of B is contained, this effect can be obtained to some extent. However, if the B content exceeds 0.010%, excessive nitrides are formed. In this case, the cold forgeability and magnetic properties of the steel material are deteriorated. Therefore, the B content is 0 to 0.010%, and if contained, the B content is 0.010% or less. The lower limit of the B content is preferably 0.001%, more preferably 0.002%, and further preferably 0.003%. The upper limit of the B content is preferably 0.009%, more preferably 0.008%, and further preferably 0.007%.

[0058] Ti: 0.010% or less Titanium (Ti) is an optional element and may not be contained. In other words, the Ti content may be 0%. When Ti is contained, Ti forms nitrides to fix N. This suppresses strain age hardening. If even a small amount of Ti is contained, the above effect can be obtained to some extent. However, if the Ti content exceeds 0.010%, excessive nitrides are formed. In this case, the cold forgeability and magnetic properties of the steel material are deteriorated. Therefore, the Ti content is 0 to 0.010%, and if contained, the Ti content is 0.010% or less. The lower limit of the Ti content is preferably 0.001%, more preferably 0.002%, and further preferably 0.003%. The upper limit of the Ti content is preferably 0.009%, more preferably 0.008%, and further preferably 0.007%.

[0059] Nb: 0.010% or less Niobium (Nb) is an optional element and may not be contained. In other words, the Nb content may be 0%. When Nb is contained, Nb forms nitrides to fix N. This suppresses strain age hardening. If even a small amount of Nb is contained, the above effect can be obtained to some extent. However, if the Nb content exceeds 0.010%, excessive nitrides are formed. In this case, the cold forgeability and magnetic properties of the steel material are deteriorated. Therefore, the Nb content is 0 to 0.010%, and if contained, the Nb content is 0.010% or less. The lower limit of the Nb content is preferably 0.001%, more preferably 0.002%, and further preferably 0.003%. The upper limit of the Nb content is preferably 0.009%, more preferably 0.008%, and further preferably 0.007%.

[0060] V:0.010% or less Vanadium (V) is an optional element and may not be contained. In other words, the V content may be 0%. When V is contained, V forms nitrides to fix N. This suppresses strain age hardening. If even a small amount of V is contained, the above effect can be obtained to some extent. However, if the V content exceeds 0.010%, excessive nitrides are formed. In this case, the cold forgeability and magnetic properties of the steel material are deteriorated. Therefore, the Nb content is 0 to 0.010%, and if contained, the V content is 0.010% or less. The lower limit of the V content is preferably 0.001%, more preferably 0.002%, and further preferably 0.003%. The upper limit of the V content is preferably 0.009%, more preferably 0.008%, and further preferably 0.007%.

[0061] [Group 3 (Ca, Te, Zr and Mg)] The chemical composition of the steel material of this embodiment may further contain Ca, Te, Zr and Mg in place of a portion of Fe. All of these elements spheroidize MnS, thereby improving the machinability and magnetic properties of the steel material.

[0062] Ca: 0.010% or less Calcium (Ca) is an optional element and may not be contained. In other words, the Ca content may be 0%. When Ca is contained, Ca spheroidizes MnS in the steel material, improving the machinability and magnetic properties of the steel material. Even if even a small amount of Ca is contained, this effect can be obtained to a certain extent. However, if the Ca content exceeds 0.010%, the machinability and magnetic properties of the steel material are rather deteriorated. Therefore, the Ca content is 0 to 0.010%, and if contained, the Ca content is 0.010% or less. The lower limit of the Ca content is preferably 0.001%, more preferably 0.002%, and further preferably 0.003%. The upper limit of the Ca content is preferably 0.009%, more preferably 0.008%, and further preferably 0.007%.

[0063] Te: 0.010% or less Tellurium (Te) is an optional element and may not be contained. In other words, the Te content may be 0%. When contained, Te spheroidizes MnS in the steel material, improving the machinability and magnetic properties of the steel material. Even if even a small amount of Te is contained, the above effects can be obtained to a certain extent. However, if the Te content exceeds 0.010%, the machinability and magnetic properties of the steel material are rather deteriorated. Therefore, the Te content is 0 to 0.010%, and when contained, the Te content is 0.010% or less. The lower limit of the Te content is preferably 0.001%, more preferably 0.002%, and further preferably 0.003%. The upper limit of the Te content is preferably 0.009%, more preferably 0.008%, and further preferably 0.007%.

[0064] Zr: 0.010% or less Zirconium (Zr) is an optional element and may not be contained. In other words, the Zr content may be 0%. When contained, Zr spheroidizes MnS in the steel material, improving the machinability and magnetic properties of the steel material. Even if even a small amount of Zr is contained, the above effects can be obtained to a certain extent. However, if the Zr content exceeds 0.010%, the machinability and magnetic properties of the steel material are rather deteriorated. Therefore, the Zr content is 0 to 0.010%, and when contained, the Zr content is 0.010% or less. The lower limit of the Zr content is preferably 0.001%, more preferably 0.002%, and further preferably 0.003%. The upper limit of the Zr content is preferably 0.009%, more preferably 0.008%, and further preferably 0.007%.

[0065] Mg: 0.010% or less Magnesium (Mg) is an optional element and may not be contained. In other words, the Mg content may be 0%. When contained, Mg spheroidizes MnS in the steel material, improving the machinability and magnetic properties of the steel material. Even if even a small amount of Mg is contained, the above effects can be obtained to a certain extent. However, if the Mg content exceeds 0.010%, the machinability and magnetic properties of the steel material are rather deteriorated. Therefore, the Mg content is 0 to 0.010%, and if contained, it is 0.010% or less. The lower limit of the Mg content is preferably 0.001%, more preferably 0.002%, and further preferably 0.003%. The upper limit of the Mg content is preferably 0.009%, more preferably 0.008%, and further preferably 0.007%.

[0066] [Group 4 (Pb)] The chemical composition of the steel material of the present embodiment may further contain Pb instead of a portion of Fe.

[0067] Pb:0.090% or less Lead (Pb) is an optional element and may not be contained. In other words, the Pb content may be 0%. When contained, Pb improves the machinability of the steel. Even if even a small amount of Pb is contained, the above effects can be obtained to a certain extent. However, Pb has a large impact on the human body and the environment. Therefore, the Pb content is 0 to 0.090%, and when contained, the Pb content is 0.090% or less. The lower limit of the Pb content is preferably 0.001%, more preferably 0.005%, and further preferably 0.010%. The upper limit of the Pb content is preferably 0.085%, more preferably 0.080%, more preferably 0.070%, more preferably 0.060%, and even more preferably 0.050%.

[0068] [(Feature 2) Number density ND of specific complex precipitates] The steel material of this embodiment further contains Bi and MnS, and has a number density ND of composite precipitates having a circle equivalent diameter of 1.0 to 10.0 μm of 0.9 to 300.0 particles / mm 2 Here, the composite precipitate containing Bi and MnS is also referred to as "specific composite precipitate" in this specification. The circle equivalent diameter means the diameter when the area is converted into a circle. The specific composite precipitate means a precipitate in which the Mn content is 1% or more, the S content is 1% or more, and the Bi content is 1 to 50% in mass % when the chemical composition of the precipitate is 100% in elemental analysis using EDX described later.

[0069] During cutting of steel, among the specific composite precipitates, Bi melts or becomes embrittled. The melting and embrittlement of Bi forms a stress concentration area between the specific composite precipitates and the base material. This promotes separation of chips from the base material. Furthermore, the effect of Bi on the magnetic properties and cold forgeability of the steel is small. Therefore, the specific composite precipitates improve chip disposal during cutting.

[0070] Among the specific composite precipitates, those having a circle equivalent diameter of 1.0 to 10.0 μm significantly contribute to improving chip disposability. Therefore, in the steel material of this embodiment, the number density ND of the specific composite precipitates having a circle equivalent diameter of 1.0 to 10.0 μm is adjusted to an appropriate range to improve the chip disposability of the steel material.

[0071] The number density ND of specific composite precipitates with a circle equivalent diameter of 1.0 to 10.0 μm is 0.9 pieces / mm 2 If the number density ND of specific composite precipitates having a circle equivalent diameter of 1.0 to 10.0 μm is less than 300.0 pieces / mm, the number of specific composite precipitates which become the starting points for the separation of chips from the base material during cutting is too small. Therefore, the chips become excessively long. As a result, sufficient chip disposability cannot be obtained. On the other hand, if the number density ND of specific composite precipitates having a circle equivalent diameter of 1.0 to 10.0 μm is less than 300.0 pieces / mm, the number of specific composite precipitates which become the starting points for the separation of chips from the base material during cutting is too small. 2 If the number density ND of specific complex precipitates with a circle equivalent diameter of 1.0 to 10.0 μm is more than 300.0 pieces / mm, there will be an excessive number of specific complex precipitates that act as starting points for the separation of the chips from the base material. In this case, the chips will be too short. If the chips are too short, clogging will occur easily during cutting, and chip disposal will be impaired. 2 If the diameter exceeds 1.0 μm, the cold forgeability and magnetic properties are also deteriorated. Therefore, the number density ND of specific complex precipitates having a circle equivalent diameter of 1.0 to 10.0 μm is 0.9 to 300.0 pieces / mm 2 It is.

[0072] The preferred lower limit of the number density ND of specific composite precipitates having a circle equivalent diameter of 1.0 to 10.0 μm is 1.9 pieces / mm 2 and more preferably 5.0 pieces / mm 2 and more preferably 10.0 pieces / mm 2 It is. The preferred upper limit of the number density ND of specific composite precipitates having a circle equivalent diameter of 1.0 to 10.0 μm is 200.0 pieces / mm 2 and more preferably 100.0 pieces / mm 2 and more preferably 50.0 pieces / mm 2 It is.

[0073] [Method for measuring the number density ND of specific composite precipitates with a circle equivalent diameter of 1.0 to 10.0 μm] The number density ND of specific composite precipitates having an equivalent circle diameter of 1.0 to 10.0 μm can be measured by the following method. When the cross section perpendicular to the axial direction of the steel material is circular, a test piece is taken that includes the central axis of the steel material and has a cross section parallel to the axial direction as the observation surface. The observation area of ​​the test piece is a depth position R / 2 in the radial direction from the surface of the steel material. Here, the R / 2 depth position means the center position of the radius. The surface of the test piece including the observation area is mirror-polished. The observation area of ​​the surface after mirror-polishing is observed at a magnification of 1000 times using a scanning electron microscope (SEM). The observation area is in the range of 0.9 mm x 2.4 mm (900 μm x 2400 μm), and the center position of the observation area is the R / 2 depth position. The observation field at 1000 times magnification is 90 μm x 120 μm. In other words, the observation area is divided into 200 observation fields, and each observation field is observed.

[0074] A backscattered electron image of each observation field is obtained. The circle equivalent diameter of each precipitate is determined in the observation field. Among the precipitates in the observation field, precipitates with a circle equivalent diameter of 1.0 to 10.0 μm are identified. Among the identified precipitates, specific composite precipitates are identified by EDX. Specifically, the chemical composition of the precipitate is analyzed using an energy dispersive X-ray analyzer (EDX: Energy Dispersive X-ray Spectrometry) attached to the SEM. At this time, the electron beam is irradiated so as to include the entire precipitate. Based on the result of EDX, the specific composite precipitate is identified. Specifically, Fe detected by EDX is regarded as a base material component and is excluded from the chemical composition of the precipitate. When the chemical composition of the precipitate excluding Fe is taken as 100%, a precipitate having a Mn content of 1% or more, a S content of 1% or more, and a Bi content of 1 to 50% in mass% is identified as a "specific composite precipitate". When the Bi content exceeds 50%, the precipitates are recognized as Bi particles rather than specific composite precipitates.

[0075] Using the above method, the total number of specific composite precipitates with a circle equivalent diameter of 1.0 to 10.0 μm is determined in an observation area of ​​0.9 mm × 2.4 mm (900 μm × 2400 μm). Based on the total number obtained and the area of ​​the observation area of ​​0.9 mm × 2.4 mm (900 μm × 2400 μm), the number density ND (number / mm ) of specific composite precipitates with a circle equivalent diameter of 1.0 to 10.0 μm is calculated. 2 ) is required.

[0076] [Effects of the steel material of this embodiment] The steel material of this embodiment satisfies Features 1 and 2. Therefore, the steel material of this embodiment has excellent cold forgeability and excellent magnetic properties, and further has excellent chip disposability.

[0077] [Applications of the steel material of this embodiment] The steel material of this embodiment is widely applicable to applications requiring excellent cold forgeability, excellent magnetic properties, and excellent chip disposal properties. The steel material of this embodiment is particularly suitable as a material for soft magnetic parts. Examples of soft magnetic parts include solenoids used in automatic transmissions, electromagnetic clutches and brakes, which are electrical components of automobiles and industrial machines, iron core materials for relays and solenoid valves, magnetic shielding materials, electric actuator materials, motor components, sensor components, etc.

[0078] The shape of the steel material of the present embodiment is not particularly limited. Preferably, the steel material of the present embodiment is a steel bar or a wire rod. More preferably, the steel material of the present embodiment is a steel bar having a circular cross section perpendicular to the axial direction.

[0079] [Preferable embodiment 1 of the steel material according to the present embodiment] Preferably, the steel material of this embodiment satisfies the characteristics 1 and 2, and further satisfies the following characteristic 3. (Feature 3) Bp defined by the formula (1) is 4.00 to 75.00. Bp = 10 × (Mn + 10 × S + 240 × Bi) (1) Here, each element symbol in formula (1) is substituted with the content of the corresponding element in mass %. Feature 3 will be explained below.

[0080] Bp is an index of chip disposability in a steel material that satisfies Features 1 and 2. If Bp is 4.00 to 75.00, the chemical composition of the specific complex precipitates falls within a more appropriate range, and the number density ND of the specific complex precipitates having a circle equivalent diameter of 1.0 to 10.0 μm falls within a more appropriate range within the range that satisfies Feature 2. As a result, chip disposability is further improved. A more preferable lower limit of Bp is 5.00, and an even more preferable lower limit is 6.00. A more preferred upper limit for Bp is 68.00, a more preferred upper limit is 56.00, a more preferred upper limit is 32.00, a more preferred upper limit is 25.00, and a more preferred upper limit is 20.00.

[0081] [Preferable embodiment 2 of the steel material according to the present embodiment] Preferably, the steel material of the present embodiment satisfies the characteristics 1 and 2, or satisfies the characteristics 1 to 3, and further satisfies the following characteristic 4. (Feature 4) The grain size number of the ferrite grains is 7 or less.

[0082] The grain size number of the ferrite grains affects the magnetic properties. When the grain size number of the ferrite grains is small, that is, when the grain size is large, the magnetic properties are improved. If the steel satisfies Features 1 and 2, or Features 1 to 3, and further, the grain size number of the ferrite grains is 7 or less, the magnetic properties of the steel are further improved.

[0083] The upper limit of the grain size number of the ferrite grains is preferably 6, and more preferably 5. The lower limit of the grain size number of the ferrite grains is not particularly limited, but is, for example, 2, and more preferably 0.

[0084] [Method for measuring the grain size number of ferrite grains] The grain size number of ferrite grains can be determined by the following method. In a cross section perpendicular to the axial direction of the steel material, a test piece is taken from an observation site corresponding to a depth of 5 mm or more from the surface. If the cross section perpendicular to the axial direction of the steel material is circular, a test piece is taken with the observation site at a depth of R / 2 from the surface of the steel material. The surface of the test piece, including the observation site, is mirror-polished. The grain size number of the ferrite grains is determined for the observation site on the surface after mirror polishing in accordance with JIS G 0551:2020. Note that nital containing nitric acid at a volume fraction of 2 to 5% is used for etching. The area of ​​the observation site is 0.5 mm2 or less. 2 The grain size number is determined by comparing it with the standard grain size chart specified in 7.2 of the above-mentioned JIS standard.

[0085] [Method of manufacturing steel material according to this embodiment] A method for manufacturing a steel material according to this embodiment will be described below. The method for manufacturing a steel material described below is one example of the method for manufacturing a steel material according to this embodiment. Therefore, a steel material having the above-mentioned configuration may be manufactured by a manufacturing method other than the manufacturing method described below. However, the manufacturing method described below is a preferred example of the method for manufacturing a steel material according to this embodiment.

[0086] An example of a method for manufacturing a steel material according to this embodiment includes the following steps. (Process 1) Refining process (Process 2) Casting process (Process 3) Hot processing process Each step will be described below.

[0087] [(Process 1) Refining process] In the refining process, molten steel whose chemical composition satisfies characteristic 1 is produced. Specifically, primary refining and secondary refining are carried out. In the primary refining, molten iron produced by a well-known method is subjected to primary refining in a converter. Furthermore, secondary refining is carried out on the molten steel tapped from the converter.

[0088] In secondary refining, alloy elements are added to the molten steel after primary refining and stirred to adjust the chemical composition of the molten steel to satisfy characteristic 1. The temperature of the molten steel in secondary refining is adjusted to 1530~1680℃. In secondary refining, the Bi in the molten steel is adjusted by adding a Bi wire to the molten steel and stirring the molten steel. The secondary refining process satisfies the following conditions 1 and 2.

[0089] (Condition 1) After Bi is added to the molten steel, the stirring time S0 (min) until the stirring is completed in the secondary refining is set to 10 to 50 min. (Condition 2) The stirring power density τ of the molten steel after adding Bi to the molten steel is set to 10 to 90 W / t. The stirring power density τ (W / t) is defined by the following formula (A). τ=0.0285×Q×T / W×LOG(1+513.5×Z / V1) (A) Here, the flow rate (NL / min) of gas injected into the ladle containing molten steel is substituted for Q in equation (A). The temperature of the molten steel (K) is substituted for T. The mass (t) of the molten steel in the ladle is substituted for W. The depth (m) of the molten steel in the ladle is substituted for Z. The degree of vacuum (torr) in the atmosphere containing the molten steel being stirred is substituted for V1. Conditions 1 and 2 will be explained below.

[0090] [Regarding condition 1] The specific composite precipitates are formed by composite precipitation of Bi particles and MnS generated during the next casting process. In the secondary refining, if the stirring time S0 from adding Bi to the molten steel until the end of stirring is less than 10 minutes, the Bi in the molten steel does not diffuse sufficiently. In this case, excessively large Bi particles are generated during the casting process, and the number density of the Bi particles decreases. As a result, it is difficult to generate a sufficient amount of the specific composite precipitates. On the other hand, if the stirring time S0 exceeds 50 minutes, the diffusion of Bi becomes excessive. In this case, the Bi particles generated during the casting process become finer, and the number density of the Bi particles increases. As a result, the specific composite precipitates are excessively generated in the manufactured steel.

[0091] If the stirring time S0 is 10 to 50 minutes, the degree of diffusion of Bi in the molten steel becomes appropriate. Therefore, the number density of Bi particles generated during the casting process is in an appropriate range. As a result, the number density of specific composite precipitates with a circle equivalent diameter of 1.0 to 10.0 μm in the manufactured steel material is in an appropriate range.

[0092] [Regarding condition 2] If the stirring power density τ of the molten steel after adding Bi to the molten steel is less than 10 W / t, Bi does not diffuse sufficiently in the molten steel. In this case, excessively large Bi particles are generated during the casting process, and the number density of the Bi particles decreases. As a result, it is difficult to generate a sufficient amount of specific composite precipitates. On the other hand, if the stirring power density τ exceeds 90 W / t, Bi diffuses excessively in the molten steel. In this case, the Bi particles generated during the casting process become finer, and the number density of the Bi particles increases. As a result, the specific composite precipitates are generated excessively in the manufactured steel. If the stirring power density τ is 10 to 90 W / t, the degree of diffusion of Bi in the molten steel becomes appropriate. Therefore, the number density of Bi particles generated during the casting process falls within an appropriate range. As a result, the number density of specific composite precipitates with a circle equivalent diameter of 1.0 to 10.0 μm falls within an appropriate range in the manufactured steel material.

[0093] [(Process 2) Casting process] In the casting process, the bloom is produced by continuous casting using molten steel at a casting speed Vc of 0.25 to 0.85 m / min.

[0094] If the casting speed Vc is less than 0.25 m / min, excessively large Bi particles are generated during the casting process, and the number density of the Bi particles is reduced. As a result, it is difficult to generate a sufficient amount of specific complex precipitates. On the other hand, if the casting speed Vc exceeds 0.85 m / min, the diffusion of Bi in the molten steel becomes excessive. In this case, the Bi particles generated during the casting process become finer, and the number density of the Bi particles increases. As a result, the specific complex precipitates are generated excessively in the manufactured steel material.

[0095] If the casting speed Vc is 0.25 to 0.85 m / min, the number density of Bi particles generated during the casting process is in an appropriate range, and as a result, the number density of specific composite precipitates having a circle equivalent diameter of 1.0 to 10.0 μm in the produced steel material is in an appropriate range.

[0096] [(Process 3) Hot processing process] The hot working step is an optional step and may not be performed. If performed, in the hot working step, hot working is performed on the slab or steel ingot produced in the casting step to produce the steel material of the present embodiment. The hot working may be hot rolling or hot forging. The hot working step includes, for example, a rough working step and a finish working step.

[0097] The rough processing step is, for example, blooming. The finish processing step is, for example, finish rolling using a continuous rolling mill, or hot forging. In the continuous rolling mill, for example, a horizontal stand having a pair of horizontal rolls and a vertical stand having a pair of vertical rolls are alternately arranged in a row. The heating temperature in the rough processing step and the finish processing step is not particularly limited. In order to prevent the specific composite precipitates from becoming coarse, the heating temperature in the rough processing step and the finish processing step is preferably 1000 to 1200 ° C., respectively. If the heating temperature in the rough processing step and the finish processing step is less than 1000 ° C., the grain size number of the ferrite grains of the manufactured steel material will be large. In addition, the steel material temperature immediately after the final reduction in the finish processing step is defined as the "finish processing temperature" (° C.). The finish processing temperature is not particularly limited, but a preferred finish processing temperature is 890 ° C. or higher. If the finish processing temperature is less than 890 ° C., the grain size number of the ferrite grains will be large.

[0098] The steel material according to this embodiment is manufactured by the above manufacturing process. The above manufacturing method is a preferred example of the manufacturing method of the steel material according to this embodiment. Therefore, the steel material having the above configuration may be manufactured by a manufacturing method other than the above manufacturing method. In short, the manufacturing method is not particularly limited as long as the steel material of this embodiment having the above configuration can be manufactured.

[0099] [Soft magnetic parts] The soft magnetic part of this embodiment is made of the steel material of this embodiment. That is, the soft magnetic part of this embodiment is manufactured using the steel material of this embodiment as a material. The soft magnetic part is manufactured, for example, by the following well-known method.

[0100] The steel material of this embodiment is subjected to wire drawing. The steel material after wire drawing is subjected to hot forging or cold forging to manufacture an intermediate product having a shape similar to that of the soft magnetic component. The manufactured intermediate product is subjected to cutting. The intermediate product after cutting is subjected to well-known magnetic annealing as necessary. The soft magnetic component is manufactured by the above-mentioned well-known manufacturing process. EXAMPLES

[0101] The effect of the steel material of this embodiment will be described more specifically with reference to examples. The conditions in the following examples are one example of conditions adopted to confirm the feasibility and effect of the steel material of this embodiment. Therefore, the steel material of this embodiment is not limited to this one example of conditions.

[0102] Steel materials having the chemical compositions shown in Tables 1A and 1B were manufactured by the following method. In the following explanation, Tables 1A and 1B are collectively referred to as "Table 1." "-" in Table 1 indicates that the content of the corresponding element is below the impurity level.

[0103] [Table 1A]

[0104] [Table 1B]

[0105] A 70-ton converter was used to carry out the refining process (primary refining and secondary refining) to produce molten steel for each test number. In the secondary refining, Bi was added to the molten steel using a wire, and stirring was performed. The stirring time S0 (min) from the addition of Bi in the secondary refining until the end of stirring, and the stirring power density τ (W / t) are shown in Table 2. The molten steel temperature in the secondary refining was 1530 to 1680°C.

[0106] [Table 2]

[0107] Blooms were produced by continuous casting using the produced molten steel. The casting speed Vc (m / min) in the continuous casting was as shown in Table 2. After heating the blooms, billets were produced by performing blooming rolling. The heating temperature of the blooms was 1000 to 1200°C. After reheating this billet to 1200°C, hot forging was performed to produce steel materials (steel bars) with a diameter of 50 mm. The finish processing temperatures of the test numbers other than test numbers 62 to 67 were 890°C or higher. On the other hand, the finish processing temperature of test numbers 62 to 67 was 850°C.

[0108] [About the evaluation test] The following evaluation tests were carried out on the steel materials with each test number. (Test 1) Measurement test of the number density ND of specific composite precipitates with a circle equivalent diameter of 1.0 to 10.0 μm (Test 2) Measurement test of grain size number of ferrite grains (Test 3) Cold forgeability evaluation test 1 (deformation resistance) (Test 4) Cold forgeability evaluation test 2 (limit compression ratio) (Test 5) Magnetic property evaluation test (Test 6) Chip disposal evaluation test

[0109] [(Test 1) Measurement test of the number density of specific composite precipitates] Based on the method described in [Method for measuring the number density ND of specific composite precipitates having a circular equivalent diameter of 1.0 to 10.0 μm] above, the number density ND of specific composite precipitates having a circular equivalent diameter of 1.0 to 10.0 μm was determined for the steel material of each test number. Note that test pieces were taken at the R / 2 position of the steel material as the observation site. The number density obtained is shown in the "Number density ND (particles / mm 2 ) column.

[0110] [(Test 2) Measurement test of grain size number of ferrite grains] Based on the method described in the above [Method of measuring grain size number of ferrite grains], the grain size number of the ferrite grains of the steel material of each test number was determined. According to the determined grain size number, the evaluation was made as follows. A: The grain size number is 7 or less. B: The grain size number is greater than 7. The evaluation results are shown in the "Grain Size Number" column in Table 2.

[0111] [(Test 3) Cold forgeability evaluation test 1 (deformation resistance)] As one of the evaluation indexes of cold forgeability, the deformation resistance of the steel material of each test number was evaluated by the following method. A test piece with a diameter of 14 mm and a height of 21 mm was prepared from the R / 2 depth position of the steel material of each test number. The test piece was prepared so that the axial direction of the test piece was parallel to the axial direction of the steel material and the central axis of the test piece was at the R / 2 depth position of the steel material. A cold compression test was performed at room temperature in the air using the prepared test piece. A 500t hydraulic press was used for the cold compression test. In the cold compression test, the load (N) was measured when the compression ratio (%) shown in formula (B) reached 70%. Compression ratio (%) = (h0-hC) / h0 × 100 (B) Here, h0 is the height of the test piece before the test (mm), and hC is the height of the test piece after compression (mm).

[0112] From the obtained load (N), the deformation resistance (MPa) shown in formula (C) was calculated. Deformation resistance (MPa)=P / Smax (C) Here, P is the load (N) at 70% compression, and Smax is the maximum cross-sectional area (mm 2 ) is substituted.

[0113] According to the obtained deformation resistance (MPa), the evaluation was made as follows. A: The deformation resistance is 600 MPa or less, and the cold forgeability is very high. B: The deformation resistance is more than 600 MPa and not more than 650 MPa, and the cold forgeability is high. C: Deformation resistance exceeds 650 MPa, and cold forgeability is poor. The evaluation results are shown in the "deformation resistance" column of the "cold forgeability" column in Table 3.

[0114] [Table 3]

[0115] [(Test 4) Cold forgeability evaluation test 2 (limit compression ratio)] As one of the evaluation indexes of cold forgeability, the limit compression ratio of the steel material of each test number was evaluated by the following method. A plurality of test pieces shown in FIG. 1 were prepared from the R / 2 depth position of the steel material of each test number. Referring to FIG. 1, the diameter D1 of the test piece was 14 mm, and the length L1 was 21 mm. The test piece was prepared so that the axial direction of the test piece was parallel to the axial direction of the steel material, and the central axis of the test piece was at the R / 2 depth position of the steel material. A notch extending in the axial direction was formed on the outer peripheral surface of the test piece. The notch angle A1 of the notch was 30°, and the curvature radius R1 of the groove bottom portion of the notch was 0.15 mm. The depth D2 of the notch was 0.8 mm.

[0116] A cold compression test was carried out using the prepared test pieces by the following method. A 500t hydraulic press was used for the cold compression test. The cold compression test was carried out on each test piece at room temperature in the air. Compression was stopped when microcracks of 0.2 mm or more were formed in the notch, and the compression ratio (%) at that time was obtained. A cold compression test was carried out on multiple test pieces, and the compression ratio (%) at which the cumulative failure probability was 50% or more, that is, the minimum compression ratio at which the number of test pieces in which cracks were confirmed was half of the total number of test pieces, was determined as the limit compression ratio (%). Evaluation was carried out according to the obtained limit compression ratio (%) as follows. A: The limit compression rate is 75% or more, and the cold forgeability is very high. B: The limit compression ratio is 65% or more and less than 75%, and the cold forgeability is high. C: The limit compression ratio is less than 65%, and the cold forgeability is poor. The evaluation results are shown in the "Limiting compression ratio" column of the "Cold forgeability" column in Table 3.

[0117] [(Test 5) Magnetic property evaluation test] The magnetic properties (magnetic flux density and coercivity) of the steel material of each test number were evaluated by the following method. From the steel material of each test number, a ring-shaped test piece as shown in FIG. 2 was prepared. The outer diameter D4 of the ring-shaped test piece was 45 mm, the inner diameter D3 was 33 mm, and the thickness T1 was 5 mm. The central axis of the ring-shaped test piece was coaxial with the central axis of the steel material.

[0118] The prepared test specimen was subjected to magnetic annealing by holding it at 850°C for 3 hours in a non-oxidizing atmosphere. A coil for applying magnetic flux was wound 200 turns on the test specimen after magnetic annealing, and further, a coil for detecting magnetic flux was wound 100 turns. Using the wound test specimen, magnetic properties were measured in accordance with JIS C 2504:2000. Specifically, an automatic magnetization measuring device (product name: SK130 manufactured by Metron Giken Co., Ltd.) was used to measure the initial magnetization curve up to an applied magnetic field of 10000A / m at room temperature. Furthermore, a hysteresis curve (BH curve) up to an applied magnetic field of 400A / m was obtained after demagnetization. From the obtained hysteresis curve, the magnetic flux density (T) and coercive force (A / m) at 10000A / m were obtained.

[0119] Depending on the obtained magnetic flux density (T), the magnetic flux density was evaluated as follows. A: The magnetic flux density (T) is 1.90 T or more, which is very high. B: The magnetic flux density (T) is 1.80 T or more and less than 1.90 T, and the magnetic flux density is high. C: The magnetic flux density (T) is less than 1.80 T, and the magnetic flux density is low. Furthermore, depending on the obtained coercive force (A / m), the coercive force was evaluated as follows. A: It is less than 60A / m as specified by the JIS SUY0 type, and has excellent coercive force. B: The magnetic strength is less than 80A / m as specified by JIS SUY1 type, and has excellent coercive force. C: Over 80A / m as specified by JIS SUY1 type, and has low coercive force. The evaluation results are shown in the "Magnetic Flux Density" and "Coercive Force" columns of the "Magnetic Properties" section of Table 3.

[0120] [(Test 6) Evaluation test for chip disposal] The chip disposability of the steel material of each test number was evaluated by the following method. A cylindrical test piece shown in FIG. 3 was prepared from the steel material of each test number. The diameter D5 of the cylindrical test piece was 50 mm, and the thickness T2 was 30 mm. The cylindrical test piece was cut at both ends perpendicular to the diameter at positions 3 mm from both ends of the diameter, and the length D6 between the cut surfaces after cutting was 44 mm. In the drilling and cutting test, the cut surface of the cylindrical test piece was clamped and fixed by a jig. The central axis of the test piece was coaxial with the central axis of the steel material.

[0121] The following drilling and cutting test was carried out on the test piece. Specifically, a high-speed drill with a diameter of 8 mm was used to drill four R / 2 depth positions at a 90° pitch around the center axis of the test piece under conditions of a peripheral speed of 30 m / min and a feed of 0.2 mm / rev to create through holes. A total of 20 through holes were created using multiple test pieces, and chips (approximately 230 g) generated in the creation of the 20 through holes were collected. The mass (g) of each of the collected chips was measured, and a histogram was created at a mass pitch of 0.01 g. Forty chips were randomly selected from the chips included in the range of the average value ±σ of the histogram. The total mass (g) of the selected 40 chips was calculated. Evaluation was performed according to the total mass (g) as follows. A: The mass is 5 to 10 g, and chip disposal is very easy. B0: Mass is 3g or more and less than 5g, and chip disposal is better. B1: Mass is between 2g and 3g, and chip disposal is easy. B2: Mass is more than 10g and less than 12g, and chip disposal is easy. C1: Mass is less than 2g and chip disposal is poor. C2: The mass is more than 12g and the chip disposal property is poor. The evaluation results are shown in the "Chip disposal" column in Table 3.

[0122] [comprehensive evaluation] The "Overall Evaluation" column in Table 3 shows an overall evaluation based on the evaluation results of the above-mentioned Tests 3 to 6. The overall evaluation is as follows. ⊚: All evaluation results are rated A. ○: At least one of the evaluation results was rated B, and no C was rated. ×: At least one of the evaluation results was rated C. If the overall evaluation was "◎" or "◯", it was determined that the steel material having that test number had excellent magnetic properties, excellent cold forgeability, and further excellent chip disposability.

[0123] [Evaluation Results] Referring to Tables 1 to 3, the steel materials of test numbers 1 to 67 satisfied features 1 and 2. Therefore, the steel materials of these test numbers had excellent magnetic properties and excellent cold forgeability, and further had excellent chip properties.

[0124] In particular, Test Nos. 1 to 55, 62, and 63 satisfied not only Feature 1 and Feature 2, but also Feature 3. Therefore, compared with Test Nos. 56 to 61 and 64 to 67 which did not satisfy Feature 3, they had excellent chip disposal properties.

[0125] On the other hand, in test number 68, the stirring time S0 was too short, and therefore sufficient chip disposal performance was not obtained.

[0126] In test number 69, the stirring power density τ was too large, and therefore sufficient cold forgeability, magnetic properties, and chip disposability were not obtained.

[0127] In test numbers 70 and 71, the stirring time S0 was too short, and therefore sufficient chip disposal was not achieved.

[0128] In test numbers 72 and 73, the stirring time S0 was too long, and therefore sufficient cold forgeability, magnetic properties, and chip disposability were not obtained.

[0129] In test numbers 74 and 75, the stirring power density τ was too small, and therefore sufficient chip disposal performance was not obtained.

[0130] In test numbers 76 and 77, the stirring power density τ was too large, and therefore sufficient cold forgeability, magnetic properties, and chip disposability were not obtained.

[0131] In test numbers 78 and 79, the casting speed Vc was too low, so sufficient chip disposability was not obtained.

[0132] In test numbers 80 and 81, the casting speed Vc was too high, and therefore sufficient cold forgeability, magnetic properties, and chip disposability were not obtained.

[0133] The embodiments of the present disclosure have been described above. However, the above-described embodiments are merely examples for implementing the present disclosure. Therefore, the present disclosure is not limited to the above-described embodiments, and can be implemented by appropriately modifying the above-described embodiments without departing from the spirit of the present disclosure.

Claims

1. The chemical composition, in mass%, is C: 0.0300% or less, Si: 0.20% or less, Mn: 0.10 to 0.50%, P: 0.030% or less, S: 0.030% or less, Al: 0.050% or less, N: less than 0.0080%, O: 0.030% or less, and Bi: 0.0010 to 0.0300%; The balance is Fe and impurities. The number density of composite precipitates containing Bi and MnS and having a circle equivalent diameter of 1.0 to 10.0 μm is 0.9 to 300.0 pieces / mm 2 That is, Steel material.

2. The chemical composition, in mass%, is C: 0.0300% or less, Si: 0.20% or less, Mn: 0.10 to 0.50%, P: 0.030% or less, S: 0.030% or less, Al: 0.050% or less, N: less than 0.0080%, O: 0.030% or less, and Bi: 0.0010 to 0.0300%; Further, the composition contains one or more selected from the group consisting of Groups 1 to 4, The balance is Fe and impurities. The number density of composite precipitates containing Bi and MnS and having a circle equivalent diameter of 1.0 to 10.0 μm is 0.9 to 300.0 pieces / mm 2 That is, Steel material. [Group 1] Cu: 0.30% or less, Ni: 0.20% or less, Cr: 0.20% or less; and Mo: 0.05% or less [Group 2] B: 0.010% or less, Ti: 0.010% or less, Nb: 0.010% or less; and V: 0.010% or less [Group 3] Ca: 0.010% or less, Te: 0.010% or less, Zr: 0.010% or less; and Mg: 0.010% or less [Group 4] Pb: 0.090% or less

3. The steel material according to claim 2, The chemical composition comprises the first group, Steel material.

4. The steel material according to claim 2, The chemical composition contains the second group, Steel material.

5. The steel material according to claim 2, The chemical composition contains the third group, Steel material.

6. The steel material according to claim 2, The chemical composition contains the fourth group. Steel material.

7. The steel material according to any one of claims 1 to 6, Bp defined by formula (1) is 4.00 to 75.00; Steel material. Bp=10×(Mn+10×S+240×Bi) (1) Here, each element symbol in formula (1) is substituted with the content of the corresponding element in mass %.

8. The steel material according to claim 1 or 2, The grain size number of the ferrite grains is 7 or less. Steel material.

9. The steel material according to claim 1 or 2, Soft magnetic parts.

Citation Information

Patent Citations

  • Hokozokuhoriamidofuirumuno seizohoho

    JP1976016363A

  • Soft magnetic low carbon steel having excellent machinability and magnetic property, production method therefor and method for producing soft magnetic low carbon steel parts obtained by using the same steel

    JP2003055745A

  • Soft magnetic steel material superior in cold forgeability, machinability and magnetic property, and soft magnetic steel parts superior in magnetic property

    JP2007046125A

  • Steel material for soft magnetic component and manufacturing method of soft magnetic component using the same

    JP2018076556A